Pengaruh Pembelajaran Learning Cycle 7E dan 5E Terhadap Kreativitas Siswa Pada Perubahan Wujud Benda - Helinah, Eliys; Jayadinata, Asep Kurnia; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2019)
The learning cycle model of 7E and 5E is learning that explores student’s abilities to their learning environment, which one become of the factors that influence student creativity. Creativity of each student is different but creativity. The method in this research is non-equivalent control group design. The population of this study was all elementary school students in the fifth grade in Suranenggala sub-district using purposive sampling technique which the study sample is class V of SDN 1 Purwawinangun class VA and VB. Research using test and non-test instruments. The test instrument consisted of student activity tests, and for non-tests are student activity, planning observation and teacher performance, field notes, teacher and student interviews. The results of the research that the learning cycle models 7E and 5E have a positive and significant influence on students creativity in the material changes in objects.